2010
DOI: 10.1007/s11250-010-9581-7
|View full text |Cite
|
Sign up to set email alerts
|

Intake and digestibility in cattle fed low-quality tropical forage and supplemented with nitrogenous compounds

Abstract: -The objective of this study was to evaluate the effects of supplementation with nitrogenous compounds on intake, digestibility, and rumen microbial synthesis in cattle fed low-quality tropical forage. Five crossbred heifers, averaging 209 kg and fitted with ruminal fistulla, were used. The animals were fed ad libitum with signal grass (Brachiaria decumbens Stapf.) hay, which had crude protein (CP) content of 5.08%, as dry matter (DM) basis. The five treatments were defined according to the increasing level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
83
1
17

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 119 publications
(109 citation statements)
references
References 27 publications
8
83
1
17
Order By: Relevance
“…Despite of constant estimate of RF 2 from 7% of CP, results reported by Sampaio et al (2009) showed that the voluntary intake of dry matter and undegradable NDF is maximized at 10% of the CP. This behavior corroborates the outflow of undegradable NDF as a determinant factor of the voluntary intake of low-quality forages.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Despite of constant estimate of RF 2 from 7% of CP, results reported by Sampaio et al (2009) showed that the voluntary intake of dry matter and undegradable NDF is maximized at 10% of the CP. This behavior corroborates the outflow of undegradable NDF as a determinant factor of the voluntary intake of low-quality forages.…”
Section: Resultsmentioning
confidence: 90%
“…It must be emphasized that the experimental diet conditions in this work and in the work of Lazzarini (2007) were atypical, where NDF from low-quality forage was basically the only source of carbohydrates for microbial growth, with non-fibrous carbohydrates (NFC) intake below metabolic fecal excretion (Lazzarini, 2007;Sampaio et al, 2009). …”
Section: Resultsmentioning
confidence: 97%
“…The authors explained the result because the bacteria that found changes in ammonia nitrogen levels in the rumen of cattle receiving protein supplementation degrade cellulose use the ammonia for growth, thus the ammonia is a limiting factor for animals on grazing, which demonstrates the importance of protein-energy supplementation in animal feed grazing. This study the with NH 3 -N centration showed average of 16.24 mg 100 mL -1 , a value considered optimal by Sampaio et al (2010) who consider 10 mg 100 mL -1 required for increased voluntary intake of dry material for animals on grazing.…”
Section: Resultsmentioning
confidence: 77%
“…There was no statistical difference (P < 0.05) for N-NH 3 concentration when 20 and 25% CP was provided at 0.5% of BW, however the latter differed from mineral mixture and supplementation of 25% CP provided at 1.0% of BW, which reached N-NH 3 concentration of 22.45 mg dL -1 . Sampaio et al (2010) found that N-NH 3 concentration of 5.00 mg dL -1 were enough to maintain adequate microbial activity in the rumen of ruminants fed with low quality tropical grasses.…”
Section: Resultsmentioning
confidence: 92%
“…Better performance of supplemented animals can be attributed to higher daily dry matter intake compared to nonsupplemented animals, allowing an increase in supply of protein (amino acids) and energy (volatile fatty acids) precursors to animals. Similarly, it can be inferred that for supplemented animals, there were higher nitrogen (N) compounds available for ruminal microflora growth, maintaining ruminal ammonia nitrogen levels above 10 mg dL -1 , proposed by Sampaio et al (2010) and Leng (1990), ranging from 13.10 to 22.45 mg dL -1 (Table 5 and 6) in supplemented animals, which probably led to an increase of fibrous carbohydrate digestion in the rumen and microbial protein flow to the abomasum. These last events may be due to an increase in performance of supplemented animals.…”
Section: Resultsmentioning
confidence: 97%